COMPARATIVE-TYPOLOGICAL STUDY OF THE PSYCHOLOGICAL CHRONOTOPE IN THE NOVELS “THE WOMAN IN WHITE” BY WILKIE COLLINS AND “NIGHT AND DAY” BY CHOLPON - Alimova, Irodakhon Zokirjon qizi; To‘rayeva , Bakhor (Educational Research in Universal Sciences, 2024)
Wilkie Collins’ “The Woman in White” and Cholpon’s “Night and Day” belong to different literary traditions and historical contexts, yet both authors engage with the psychological dimensions of their characters in profound ways. The analysis explores how the authors construct and manipulate the psychological chronotope, shedding light on the impact of time, space, and the characters’ internal landscapes on the unfolding narrative. The study employs a multidisciplinary approach, drawing on literary theory, psychology, and cultural studies to enrich the analysis of the chosen novels. This comparative-typological study not only enhances our appreciation of the chosen works but also offers insights into the broader implications of employing the psychological chronotope as a narrative tool in literature.